1998
DOI: 10.1071/bt97056
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale Genetic Structure of Eucalyptus globulus ssp. globulus Forest Revealed by RAPDs

Abstract: Fine-scale genetic structure in Eucalyptus globulus ssp. globulus native forest was detected using 69 randomly amplified polymorphic DNA (RAPD) markers. The association between genetic similarity and geographic distance was studied among 51 trees from the Tinderbox locality in Tasmania (distance ranging from 2 m to 4 km apart) and compared to 18 trees from localities up to 100 km away. Twenty pedigreed F1s were used as controls to scale the RAPD similarity among individuals to pedigree similarity. The associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 37 publications
6
38
0
Order By: Relevance
“…FPC concentrations are highly heritable in Eucalyptus (Andrew et al 2005), and Andrew et al (2007) showed in E. melliodora that strong spatial autocorrelation in FPC concentrations overlaid a highly congruent spatial structure in genetic variance. The strength and scale of autocorrelation observed in this study for FPCs are comparable to those in E. melliodora and those for genetic markers in Tasmanian E. globulus (Skabo et al 1998), and are probably largely a product of isolation by distance (Heywood 1991). In addition to endogenous genetic factors, however, it is also conceivable that exogenous factors have contributed to the observed spatial structure, either through geographical heterogeneity in natural selection (Endler 1977, Linhart andGrant 1996) or through environmental influences on phenotypes (Gram andSork 2001, Brenes-Arguedas andColey 2005).…”
Section: Discussionsupporting
confidence: 62%
“…FPC concentrations are highly heritable in Eucalyptus (Andrew et al 2005), and Andrew et al (2007) showed in E. melliodora that strong spatial autocorrelation in FPC concentrations overlaid a highly congruent spatial structure in genetic variance. The strength and scale of autocorrelation observed in this study for FPCs are comparable to those in E. melliodora and those for genetic markers in Tasmanian E. globulus (Skabo et al 1998), and are probably largely a product of isolation by distance (Heywood 1991). In addition to endogenous genetic factors, however, it is also conceivable that exogenous factors have contributed to the observed spatial structure, either through geographical heterogeneity in natural selection (Endler 1977, Linhart andGrant 1996) or through environmental influences on phenotypes (Gram andSork 2001, Brenes-Arguedas andColey 2005).…”
Section: Discussionsupporting
confidence: 62%
“…1). In most cases, trees sampled were at least 100 m apart to avoid sampling closely related trees (see Skabo et al 1998). Twenty-eight trees from the Jeeralang provenance were sampled, as were 20-37 trees each of "core" ssp.…”
Section: Plant Materialsmentioning
confidence: 99%
“…These techniques have been applied to wild species to answer specific questions, mainly regarding the crossing system (Hayward and Hamilton, 1997). Some studies based on microsatellites have been employed in the study of natural populations (Collevatti et al, 2001;Zucchi et al, 2003) but most of the studies are performed with RAPD markers in plants (Chalmers et al, 1992;Wolf andRijn, 1993, Bucci andMenozzi, 1995;Yeh et al, 1995;Maguire and Sedgley 1997;Gillies et al, 1997, Palácios andGonzález-Candelas, 1997;Gallois et al, 1998, Cattan-Toupance et al, 1998, Skabo et al, 1998, and in other organisms (Peever andMilgroom, 1994, Lou et al, 1998).…”
Section: Introductionmentioning
confidence: 99%